The Effectiveness of a Training Program Based on Theory of Mind in Developing of Emotional Discrimination among Children with Autism Spectrum Disorder - Alshirawi, Maryam; Hajji, Huda (European Scientific Journal, ESJ, 2023)
Weakness in the skill of Emotional Discrimination is one of the obstacles that stand in the way of interaction and social communication of children with autism spectrum disorder, and for its development, it is necessary to prepare a program that helps improve deficiencies and gives good indicators of program performance. This study explored the effectiveness of a training program based on a theory of mind on the development of deficiencies in the skill of emotional discrimination. The study is consistent with previous studies and adds to the limited literature on the experience of developing emotional discrimination in children with autism spectrum disorder. The results could be useful in improving social interaction and supporting children’s expression and emotional expression needs, which in turn reduces their social and communication deficits.